Chapter Storia di un paradosso. Il mito di Giorgio Luti in Età Moderna - Manenti, Lorenzo (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The essay resumes, with new historical sources, the research concerning the biography of the Sienese Jesuat Giorgio Luti, the prophecy of 1491 attributed to him and the exegetical evolution of this text in the Modern Age, published in Giorgio Luti da Siena a Lucca. Il viaggio di un mito fra Umanesimo e Controriforma, Siena, Accademia degli Intronati (Monografie di storia e letteratura senese, XV) 2008. The essay is divided into two parts. The first is a study of historical sources on Giorgio Luti in the Venetian area. The second part is dedicated to the study of historians from Lucca who lived between the XVI and XVIII centuries: Gherardo Sergiusti, Giovanni Cividale, Giuseppe Bonafede and Giovanni Domenico Mansi. They paid attention to the content of the Sienese prophecy for the description about wars and devastation of the Towers of Lucca, the conversion of Islamic peoples to Christianity, thanks to a company of Lucca men and women, attributing a meaning of political pacification and religious palingenesis. Overall, however, the evolution of the myth about Giorgio Luti, paradoxically, reflects in particulary the identity crisis of the Jesuats between the XV and XVI centuries.